Implementasi Proses Penyelesaian Kasus Perceraian bagi Narapidana - Dewi, Shinta; Yusmad, Muammar Arafat; Assaad, A. Sukmawati; Mustaming; Takdir; Amir, Rahma (LP2M IAIN Palopo, 2025)
This research aims to describe the resolution of divorce cases for prisoners. The research uses qualitative with a normative juridical and sociological approach. The data source in the research comes from interviews with Heads of Correctional Institutions, Officers and Prisoners. The results of the research show that 1) Divorce processes involving prisoners as defendants often present decisions in the form of verstek decisions because prisoners or convicts are serving their sentences in prison. Because of their absence and without representing their attorney, the Legal Council will decide the case in verstek. The Defendant's limitations in attending the trial result in the principle of justice not being fulfilled for prisoners or inmates in defending their rights at trial. 2) The factors that influence the divorce of inmates at the Class II A Palopo Penitentiary are largely attributed to economic pressure, as well as a lack of social support from the community, which is why the wife asks for a divorce. 3) Efforts to facilitate the process of resolving inmate divorce cases at the Class II A Palopo Penitentiary are a) Meeting economic needs, prisoners' wives have difficulty financing the improvement in life skills that must be provided or facilitated. b) family and community support. c) Accepting that the Justice Council will decide the case in verstek because there are no provisions in the statutory regulations that regulate prisoners or convicts being able to attend divorce trials.